An Investigation of 1.8L Turbocharged Engine on Performance Using the Fuel Oil Blends in Malaysian Commercial Fuels - S. M., Rosdi; R., Mamat; Erdiwansyah, .; Ilham, Maulana; Asri, Gani; Hilmi, . (fazpublishing.com, 2023)
Researchers have been particularly interested in using alternative energy sources in internal combustion engines to reduce reliance on fuel-derived energy sources. The fusel oil, on the other hand, is a different alternative energy source that is produced as a by-product during the fermentation of alcohol and can be used in internal combustion engines. Fusel oil is a blend of high alcohols that is dark brown in colour and strongly scented. The objective of the study is to evaluate the engine performance using blends fusel oil 10% in variable commercial RON 95 and RON 97. The performance and combustion of a 1.8L Mitsubishi engine were studied. The engine was operated at a speed of 2000 RPM with a 30% throttle load. The engine study concentrated on the In-cylinder Pressure, Coefficient of Variation (COV), Rate of Pressure Rise ROPR), Mass Fraction Burn (MFB) and Rate of Heat Release (ROHR). As a result, the engine show that using the RON97 blends is better compared to the performance of RON95 blends. Indeed, due to the oxygen content in the blended fuel, the engine performance and emission become better than the commercial fuels.